Study on the valveless and purgeless scheme to produce high frequency detonations in a long duration. (15th December 2019) - Wang, Ke; Wang, Zhicheng; Zhao, Minghao; Sun, Tianyu; Tan, Fengguang; Zhu, Yiyuan; Lu, Wei; Yu, Xiaodong; Sha, Yu; Fan, Wei
Abstract: High frequency and long duration operations are the ultimate objective for the considerable efforts in developing practical pulse detonation engines (PDEs). Previous works have demonstrated that the valveless and purgeless scheme has a great advantage in reducing the hardware complexity to achieve high frequency detonations. However, the great challenge arises in the implementation of long duration operation. Therefore, the present work aims at clarifying the key factor that significantly impacts the long duration of detonations. In this study, the detonation tube wall thickness, the type of obstacles for promoting the deflagration to detonation transition (DDT) process, and the closed end structure have been parametrically checked regarding their influence on the duration of detonations. The results from experiments showed that, although the wall thickness has little impact on the operating time, a conical diffuser properly designed is found to be able to greatly increase the operating frequency and improve the supply pressure ceiling, as a result of the creation of an efficient buffer zone. Actually, long duration detonations of 49 s at 90 Hz were achieved when the conical diffuser with a semi-angle of 5° was utilized. Finally, it is proposed that comprehensive cooling should be considered in long duration detonations. Highlights: The valveless and purgeless scheme is used focusing on long duration detonations. The wall thickness has little impact on the operating time of producing detonations. A conical closed end structure is better due to efficient creation of the buffer zone. Pre-ignition will happen when the wall temperature exceeds the ignition point. Comprehensive cooling measures should be considered in long duration detonations.